Humanitarian actions of a cultural center during the Covid-19 pandemic: an analogy with supply chain business processes - Mauro Vivaldini; Maria da Penha Melo Malda Iglesias (Journal of Humanitarian Logistics and Supply Chain Management)
Purpose – This study intends to map the supply chain and characterize the business processes of a cultural center in an aggregated and coordinated operation to serve families in need during the Covid-19 pandemic. This case study analyzes distinct aspects of humanitarian management capable of contributing to the management of commercial supply chains. Design/methodology/approach – Adopting a case study approach, this research contextualizes the view on humanitarian supply chains related to the importance of participating organizations' engagement and the relationship and similarity with business organizations. Findings – The study presents the model adopted to undertake the aid operations, maps the cultural center's humanitarian supply chain, clarifies the relationships and operations developed and compares the business processes with those of commercial chains. Possibilities and initiatives are discussed that can contribute to business organizations' greater engagement in humanitarian actions. Research limitations/implications – Restricted to one case involving the cultural center and the other agents researched, the information and considerations are limited, and any generalization should be treated with caution. Practical implications – The study is a practical example that clarifies how business organizations can engage in the supply chain of humanitarian institutions. It also illustrates ways to help these institutions improve their fund-raising initiatives. Social implications – This study is justified by the representativeness of humanitarian actions in critical periods such as the Covid-19 pandemic. The study also presents potential ways to contribute to operations of this nature and to encourage business organizations to improve participation in humanitarian movements. Originality/value – Many studies on the subject have highlighted the importance of comparing humanitarian and business supply chains through real case research.